Localized Chronic Form of Langerhans Cell Histiocytosis in the Femur of a 16-Year-Old Male Successfully Treated with Radiofrequency Ablation - Kyriakos Papavasiliou; Antonia Bintoudi; Apostolos Vlahodimos; Eleftherios Tsiridis; Prodromos Hytiroglou; Ioannis Tsitouridis; Fares Sayegh (Case Reports in Oncological Medicine)
Only three cases of patients suffering from a localized chronic form of Langerhans cell histiocytosis (LCH) successfully treated with radiofrequency ablation (RFA) have been published so far. This is the first case report of a patient with a localized chronic form of LCH of the femur, which was successfully treated with percutaneous image-guided RFA, and who was evaluated pre-RFA and followed up post-RFA for a period of 48 months, in order to validate the safety and efficacy of this method and to obtain imaging studies depicting the actual in situ changes taking place post-RFA. RFA was proved to be a safe and efficient method when treating patients with a localized chronic form of LCH.